Targeting a scavenger receptor on tumor-associated macrophages activates tumor cell killing by natural killer cells - Eisinger, Silke (Proc Natl Acad Sci U S A, 2020)
Tumor-associated macrophages (TAMs) can have protumor properties, including suppressing immune responses, promoting vascularization and, consequently, augmenting tumor progression. To stop TAM-mediated immunosuppression, we use a novel treatment by injecting antibodies specific for scavenger receptor MARCO, which is expressed on a specific subpopulation of TAMs in the tumor. We now report the location of this TAM as well as the pleiotropic mechanism of action of anti-MARCO antibody treatment on tumor progression and further show that this is potentially relevant to humans. Using specific targeting, we observed decreased tumor vascularization, a switch in the metabolic program of MARCO-expressing macrophages, and activation of natural killer (NK) cell killing through TNF-related apoptosis-inducing ligand (TRAIL). This latter activity reverses the effect of melanoma cell-conditioned macrophages in blocking NK activation and synergizes with T cell-directed immunotherapy, such as antibodies to PD-1 or PD-L1, to enhance tumor killing. Our study thus reveals an approach to targeting the immunosuppressive tumor microenvironment with monoclonal antibodies to enhance NK cell activation and NK cell-mediated killing. This can complement existing T cell-directed immunotherapy, providing a promising approach to combinatorial immunotherapy for cancer.